KAJIAN SUMBER LIMBAH B3 PADA INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) SEWON - , Vikri Febriyanto; , Prof. Dr. Ir. Sunjoto, Dip.HE., DEA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Sewon wastewater treatment plant was functioned as domestik waste with organic substances content of human discharge. Based on the existing data the waste water coming in and out and the resulting sludge of the Sewon waste water treatment installation contained heavy metals were classified into hazardous and toxic (Bahan Berbahaya dan Beracun [B3]). This research aim to identifying the hazardous and toxic waste source in order to find out the kind of the compound and the metal concentration of the Sewon waste water treatment installation and technical solutions that can be done by the relevant stakeholders. The data was collected using purposive sampling. The sampling was carried out on the basis of the industri locations through which the Sewon waste water treatment installation network went and the possibility that the industries organized their production process. Subsequently, the samples were tested in laboratory. The parameters of the tested waste water were adjusted to the kinds of the industries, the raw materials used and the production process of the industries. The results of the study showed that essentially one of the characteristics of the domestik waste water was heavy metal content. The heavy metals came not only from domestik waste, but also from industries. The industri discharging their waste into IPAL Sewon network was of the kind of batik one. Meanwhile, the leathier tanning industri was only suspected to discharge the waste to the IPAL Sewon because of the limited access to the industri. The Ni content of the effluent of the batik industri was 0.909 mg/l and the Cr content of the effluent of the leather tanning industri was 11.714 mg/l. It was necessary for the industries to improve their waste treatment installation to reduce the hazardous and toxic waste impact. Additionally, it was also necessary for the Balai IPAL Sewon to formulate new SOP and to regularly monitor the industrial waste.